2018
DOI: 10.5935/0103-507x.20180010
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of delirium using the PRE-DELIRIC model in an intensive care unit in Argentina

Abstract: ObjectiveTo describe the incidence of and risk factors for delirium in the intensive care unit of a tertiary care teaching hospital in Argentina and to conduct the first non-European study exploring the performance of the PREdiction of DELIRium in ICu patients (PRE-DELIRIC) model.MethodsProspective observational study in a 20-bed intensive care unit of a tertiary care teaching hospital in Buenos Aires, Argentina. The PRE-DELIRIC model was applied to 178 consecutive patients within 24 hours of admission to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…In the ICU, the PRE-DELIRIC model 68 , which is based on ten risk factors (age, APACHE-II score, admission group, coma, infection, metabolic acidosis, use of sedatives and morphine, urea concentration and urgent admission) identified within 24 hours of ICU admission, predicted delirium with an area under the receiver operating curve of 0.87 (95% CI 0.85-0.89) in the first 24 hours after admission to the ICU. The PRE-DELIRIC model showed excellent performance in clinical cohorts, including in studies from Lithuania, Scotland and Argentina [69][70][71] .…”
Section: Prediction Modelsmentioning
confidence: 99%
“…In the ICU, the PRE-DELIRIC model 68 , which is based on ten risk factors (age, APACHE-II score, admission group, coma, infection, metabolic acidosis, use of sedatives and morphine, urea concentration and urgent admission) identified within 24 hours of ICU admission, predicted delirium with an area under the receiver operating curve of 0.87 (95% CI 0.85-0.89) in the first 24 hours after admission to the ICU. The PRE-DELIRIC model showed excellent performance in clinical cohorts, including in studies from Lithuania, Scotland and Argentina [69][70][71] .…”
Section: Prediction Modelsmentioning
confidence: 99%
“…The reported delirium rate in intensive care units has quite a wide range at 10% to 80% and it is important to have a measurement that can easily detect delirium, as it is vital for the condition's follow-up, treatment and care. 19,20,21 Delirium development is affected by many factors and its prediction and prevention will enable decreasing the rate of disorders that could lead to patient mortality and morbidity. 14 Some evidence reports that delirium increases the length of the hospital stay, increases the risk of transmission of hospital infections, and puts the patient at risk of pressure ulcers and injuries.…”
Section: Discussionmentioning
confidence: 99%
“…In this review, 14 studies reported model development (21)(22)(23)(24)(25)(27)(28)(29)(30)32,36,(39)(40)(41), and 19 studies reported model validation (21)(22)(23)(25)(26)(27)(28)(29)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41). The method of model development was logistic regression.…”
Section: Statistical Methods Of Modelsmentioning
confidence: 99%
“…The ROB and clinical applicability were assessed with (21,22,36), and the regression coefficients in the final model were adjusted in another three studies (27,39,41). In terms of predictors and outcomes, the risk of bias was unclear in six articles (26,27,30,(33)(34)(35) because they did not report blind methods in the literature. Details were shown in Appendix 1.…”
Section: Study Qualitymentioning
confidence: 99%